The Small RNA CyaR Activates Translation of the Outer Membrane Haem Receptor chuA in Enterohemorrhagic Escherichia coli - Sy, Brandon M.; Tree, Jai J. (Frontiers in Microbiology, 2022)
To sense the transition from environment to host, bacteria use a range of environmental cues to control expression of virulence genes. Iron is tightly sequestered in host tissues and in the human pathogen enterohaemorrhagic E. coli (EHEC) iron-limitation induces transcription of the outermembrane haem transporter encoded by chuAS. ChuA expression is post-transcriptionally activated at 37oC by a FourU RNA thermometer ensuring that the haem receptor is only expressed under low iron, high temperature conditions that indicate the host. Here we demonstrate that expression of chuA is also independently regulated by the cAMP-responsive sRNA CyaR and transcriptional terminator Rho. These results indicate that chuAS expression is regulated at the transcription initiation, transcript elongation, and translational level. We speculate that additional sensing of the gluconeogenic environment allows further precision in determining when EHEC is at the gastrointestinal epithelium of the host. With previous studies, it appears that the chuAS transcript is controlled by eight regulatory inputs that control expression through six different transcriptional and post-transcriptional mechanisms. The results highlight the ability of regulatory sRNAs to integrate multiple environmental signals into a layered hierarchy of signal input.